2007
DOI: 10.1016/j.jhse.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Medial Sural Artery Perforator Flap for Repair of the Hand

Abstract: We report our experience of using the medial sural artery perforator flap in the reconstruction of soft tissue defects in the hand in seven cases with 1 to 2 year follow-up. The flap is harvested from the posteromedial aspect of the leg, just below the knee and superficial to the medial head of the gastrocnemius muscle. It is based on the perforator arteries and veins supplied by the medial sural artery. The flaps ranged in size from 14 x 10 cm to 8 x 6 cm. The donor area was closed directly or by a skin graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…neck and limb reconstruction. [6][7][8][9][10][11]14 Inclusion of the plantaris tendon, sural nerve, and gastrocnemius muscle increases its versatility as a chimeric flap. 15,16 Despite its advantages, concerns limiting its use include the variability of its vascular anatomy and the need for intramuscular dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neck and limb reconstruction. [6][7][8][9][10][11]14 Inclusion of the plantaris tendon, sural nerve, and gastrocnemius muscle increases its versatility as a chimeric flap. 15,16 Despite its advantages, concerns limiting its use include the variability of its vascular anatomy and the need for intramuscular dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor & Daniel 1 first suggested the medial sural vessels as the basis of a new flap donor site in 1975 and, two decades later, Montegut 2 presented the first clinical cases of the medial sural artery perforator flap. Subsequently, Cavadas 3 and other authors [4][5][6][7][8][9][10][11] reported small clinical series of its use and emphasized its many advantages and limited donor morbidity. In situations when a thin and pliable flap is needed, the radial forearm flap has traditionally been the choice flap.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [22] have similarly used only the medial sural artery perforator (MSAP) free flap for the hand. Pedicled paraumbilical perforator-based flaps from the abdomen, Figure 1 Schematic listing of the source vessel and muscle traversed (subscript) for most presently described muscle perforator flaps.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Hallock (2001 and Cavadas et al (2001) published a more extensive study about the mapping of the sural artery perforators, where also a series of six successful clinical cases of the medial sural artery perforator (MSAP) flaps, including five free flaps and one pedicled flap for ipsilateral lower-leg and foot reconstruction were included. Since then, other manifold studies assessed the anatomical basis of the MSAPs (Kao, Chang, Chen, Wie, & Cheng, 2010;Kim, Jeong, Seul, & Cho, 2006;Kosutic, et al, 2012;Okamoto, Sekiya, Mizutani, & Otsuka, 2007;Shimizu, Kato, Sato, & Taneda, 2009;Thione, Valdatta, Buoro, Tuinder, Mortarino, & Putz, 2004;Wong, Wong, Tan, Chew, & Tay, 2012) and its clinical versatility (Cavadas et al, 2001;Chen, Chen, & Lee, 2005; Chen, Chuang, Chou, Chen, & Wang, 2005;Chen, Yu, Chang, Deng, Wu, & Chen, 2008;Choi, Nam, Choi, Roh, Kim, & Hong, 2013;Hallock, 2014;He, Jin, Zhang, & Zhang, 2014;Ives & Mathur, 2015;Kao et al, 2010;Kim et al, 2006;Lin, Lin, Lin, Hsu, Ng, & Wei, 2011;Kao, Chang, Wie, & Cheng, 2009;Kim, Hwang, Kim, & Lee, 2009;Mao, Zhang, Cui, Peng, Wang, Yu, 2011;Nugent, Endersby, Kennedy, & Burns, 2015;Song, Wu, Zhang, Chen, Ding, Ye, Wu, & Yuan, 2015;Wong et al, 2012;Xie, & Chai, 2012;Xie, Gu, Gong, & Tang, 2007;Wang, Mei, Pan, Chen, Zhang, & Tang, 2013;Zheng, Liu, Dai, & Schilling, 2015).…”
mentioning
confidence: 99%